STUDY OF INDUCED POLYGENIC VARIABILITY IN M 1 AND CHLOROPHYLL MUTATIONS IN M 2 GENERATIONS IN AROMATIC RICE - SATISH KR. CHAKRAVARTI,; SANJEEV SINGH,; H. KUMAR,; J. P. LAL,; MANISH K.VISHWAKARMA, (The Bioscan, 2012)
Variability induced for quantitative characters (days to 50% flowering, days to maturity, plant height, panicle length, panicle bearing tillers per plant and grain yield per plant.) were assessed on individual plant basis in M1 generation. The maximum frequency of chlorophyll mutations per 100M2 plants obtain in M2 generation in 20kR gamma rays + EMS (0.2%) in Kalanamak following by Badshah Bhog, respectively. The Frequency and spectrum of viable mutations per 100M2 plant maximum in 40kR gamma rays+ EMS (0.2%) in Badshah Bhog genotypes were observed in M2 generation. Among chlorophyll mutations, Albino mutant was most frequent in both the genotypes. The different types of chlorophyll mutations observed in M2 generation were Albino, Xantha, Striata and Viridis.